Training situational awareness to reduce surgical errors in the operating room. Issue 1 (9th October 2014) - Graafland, M; Schraagen, J M C; Boermeester, M A; Bemelman, W A; Schijven, M P
Abstract: Background: Surgical errors result from faulty decision-making, misperceptions and the application of suboptimal problem-solving strategies, just as often as they result from technical failure. To date, surgical training curricula have focused mainly on the acquisition of technical skills. The aim of this review was to assess the validity of methods for improving situational awareness in the surgical theatre. Methods: A search was conducted in PubMed, Embase, the Cochrane Library and PsycINFO® using predefined inclusion criteria, up to June 2014. All study types were considered eligible. The primary endpoint was validity for improving situational awareness in the surgical theatre at individual or team level. Results: Nine articles were considered eligible. These evaluated surgical team crisis training in simulated environments for minimally invasive surgery (4) and open surgery (3), and training courses focused at training non-technical skills (2). Two studies showed that simulation-based surgical team crisis training has construct validity for assessing situational awareness in surgical trainees in minimally invasive surgery. None of the studies showed effectiveness of surgical crisis training on situational awareness in open surgery, whereas one showed face validity of a 2-day non-technical skills training course. Conclusion: To improve safety in the operating theatre, more attention to situational awareness is needed in surgical training. Few structured curricula have been developed and validation research remains limited. Strategies to improve situational awareness can be adopted from other industries. Abstract : New area for improvement